Fabrication of three dimensional carbon nanotube foam by direct conversion carbon dioxide and its application in supercapacitor. (10th March 2015) - Wang, Chunlei; Li, Fangtao; Qu, Haili; Wang, Yanan; Yi, Xiaolei; Qiu, Yang; Zou, Zhijun; Luo, Yongsong; Yu, Benhai
Highlights: 3D carbon nanotube foams (CNTF) are obtained by directly conversing CO2 . As-grown CNTF can be used as a current collector for supercapacitors to substitute metal one. Binder-free porous Ni(OH)2 nanosheet array are fabricated on the CNTF. Enhanced electrical conductivity leads to excellent electrochemical performance. The present method maybe a general strategy for fabricating other 3D macroscopic structures. Abstract: Carbon nanotube (CNT) is an ideal electrode material for supercapacitors due to its low electronic and ionic charge-transfer resistances. Here we reported the direct synthesis 3D carbon nanotube foam (CNTF) macrostructure by conversing CO2 through template-directed chemical vapour deposition. Using this unique network structure and outstanding electrical and mechanical properties of the CNTF, as an example, we demonstrate the excellent electrochemical properties of Ni(OH)2 /CNTF composite. Based on the total mass of the electrode, as high as specific capacitances of 259 and 131 F g −1 are obtained at current densities of 0.5 and 10 A g −1 respectively. Meanwhile, the electrode also exhibits excellent long cycle life along with 94.0% specific capacitance retained after 2000 cycle tests. Moreover, this template-directed CVD technique is versatile and scalable, and can be a general strategy for fabricating a broad class of three-dimensional macroscopic structures of determined shapes with excellent properties and new uses.